Risk factors for sleep problems in infants - Hesti Lestari; Audrey Mety Iriani Wahani; Rocky Wilar; Permatami Herwansyah (Paediatrica Indonesiana, 2020)
Background Sleep disorders in infants can cause developmental problems, suboptimal growth, behavioral disorders, fatigue, irritability, impulsiveness, and poor mother-infant bonding. Objective To evaluate possible risk factors for sleep disorders in infants. Methods This cross-sectional study was conducted in healthy infants aged 3-6 months. Subjects were selected using proportional random sampling from four different primary healthcare facilities in Manado, North Sulawesi. Their parents completed the Brief Infant Sleep Questionnaire. Sleep disorder was defined as the presence of one or more conditions including sleep duration less than 9 hours at night (from 19.00 until 07.00), waking up at night (from 22.00 until 06.00) more than 3 times, and more than 1 hour waking at night. Results Of 112 subjects, 58 (51.8%) were male. Subjects’ mean age was 4.21 (SD 0.829) months and 76 (67.86%) experienced sleep disorders. Sleep disorders had significant associations with low socioeconomic status (OR 17; 95%CI 3.8 to 75.8), middle school or lower maternal education (OR 44.5; 95%CI 9.8 to 202), non-supine sleeping position (OR 8.8; 95%CI 1.9 to 39.7), parental use of electronic devices (OR 156.2; 95%CI 35.1 to 692.9), and non-exclusive breastfeeding (OR 85.2; 95%CI 21.1 to 344.2). Correlative analyses also revealed that electronic media usage had the strongest association with sleep disorders, followed by breastfeeding pattern, maternal education, socioeconomic status, and sleeping position ( 0.839, 0.771, 0.624, 0.433, and 0.309, respectively). However, there were no significant correlations upon multivariate analysis. Conclusion Parental use of electronic media before sleeping is the strongest risk factor for sleep disorders among infants, followed by non-exclusive breastfeeding pattern, low maternal education, low socioeconomic status, and non-supine sleeping position. However, none of these correlations were significant upon multivariate analysis, this show that all these factors influence sleep together